An Ultraviolet Survey of the DA White Dwarf Population of the Galaxy - Wall, Renae E. (My University, 2023)
DA white dwarfs are the most common type of white dwarf in our Galaxy. Hence, it is important to study the DA white dwarf population as thoroughly as possible. In this dissertation, I present our work using the Galaxy Evolution Explorer (GALEX) data to study the DA white dwarf population in the ultraviolet. I begin by presenting our use of 1837 DA white dwarfs with high signal-to-noise ratio spectra and Gaia parallaxes to verify the absolute calibration and extinction coefficients for GALEX. We use white dwarfs within 100 pc to verify the linearity correction to the GALEX data. We find that the linearity correction is valid for magnitudes brighter than 15.95 and 16.95 for the far-ultraviolet (FUV) and near-ultraviolet (NUV) bands, respectively. We also use DA white dwarfs beyond 250 pc to calculate extinction coefficients in the FUV and NUV bands: R_FUV = 8.01 +/- 0.07 and R_NUV = 6.79 +/- 0.04. These are consistent with the predicted extinction coefficients for Milky Way-type dust in the FUV, but smaller than predictions in the NUV. With well understood optical spectra and state-of-the-art model atmosphere analysis, these white dwarfs currently provide the best constraints on the extinction coefficients for the GALEX data. I then present our detailed model atmosphere analysis of 14001 DA white dwarfs from the Montreal White Dwarf Database with ultraviolet photometry from the GALEX mission. We use the 100 pc sample, where the extinction is negligible, to demonstrate that there are no major systematic differences between the best-fit parameters derived from optical only data and the optical + UV photometry. GALEX FUV and NUV data improve the statistical errors in the model fits, especially for the hotter white dwarfs with spectral energy distributions that peak in the UV. Fitting the UV to optical spectral energy distributions also reveals UV-excess or UV-deficit objects. We use two different methods to identify outliers in our model fits. Known outliers include objects with unusual atmospheric compositions, strongly magnetic white dwarfs, and binary white dwarfs, including double degenerates and white dwarf + main-sequence systems. We present a list of 89 newly identified outliers based on GALEX UV data; follow-up observations of these objects will be required to constrain their nature. I then conclude by discussing future work in UV observations of white dwarfs. Several current and upcoming large scale spectroscopic surveys are targeting $>10^5$ white dwarfs. In addition, the ULTRASAT mission is planning an all-sky survey in the NUV band. A combination of the UV data from GALEX and ULTRASAT and optical data on these large samples of spectroscopically confirmed DA white dwarfs will provide an excellent opportunity to identify unusual white dwarfs in the solar neighborhood.
Keywords: Physics, Astronomy and Astrophysics.; White dwarf stars; Ultraviolet